Electrochemical characterization of polylactic acid-block-poly(2-vinylpyridine)/gold nanoparticle (aunp) composites for glucose biosensor development - Long, JiaJia; Wan Salim, Wan Wardatul Amani; Ali, Fathilah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Nanocomposites that consist of diblock copolymer (BCP) and gold nanoparticles (AuNPs) can be applied as a suitable matrix to immobilize enzymes or other molecules based on the well-defined core/shell nanostructures of these composites. In this research, polylactic acid-block-poly(2-vinylpyridine) (PLA-b-P2VP)/hydrogen tetrachloroaurate(III) hydrate (HAuCl4.3H2O) composites were hybridized and then reduced in dichloromethane (DCM) solution. The hybridizations between gold precursors and the P2VP domain were prepared with different ratios of gold to P2VP block (1:1, 1:5, 1:10, 5:1, 10:1) by taking advantage of the association between the long-pair nitrogen of the pyridine group of P2VP. The reduction of the Au3+/PLA-bP2VP composite was accomplished by hydrazine solution in order to get gold nanoparticle/PLA-b-P2VP composites, visually confirmed by a direct color change from bright yellow to purple. In this work, ultraviolet–visible (UV-vis) spectroscopy and Fourier transform infrared spectroscopy (FTIR) were used to confirm the association between gold precursors and pyridine groups as well as the synthesis of gold nanoparticles. Furthermore, the electrochemical properties of gold nanoparticle/BCP composites with different ratios were obtained via cyclic voltammetry measurement. This composite has high potential to be used in the development of a glucose biosensor.